2022
DOI: 10.1039/d2nj01748b
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically recyclable core–shell MOF nanoparticles of Fe3O4@PDA@UIO-66-NH2 grafted by organic acids for intensified cationic dye adsorption

Abstract: Two kinds of hierarchical magnetic metal-organic framework (MOF) nanoparticles Fe3O4@PDA@UIO-66-NH-tar (mUIO-66-NH-tar) and Fe3O4@PDA@UIO-66-NH-citr (mUIO-66-NH-citr) were fabricated through post- synthetic modification. The novel nanoparticles were then characterized using SEM, FTIR, PXRD,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…P‐UiO‐66(200) has a higher weight loss because of foreign organic compounds derived from the grafted TDPA molecules on the material surfaces. Previous studies have reported a similar common phenomenon after introducing new guest organic species in MOFs [2b,15a,26] . TGA analysis results confirm the successful grafting of TDPA on UiO‐66.…”
Section: Resultssupporting
confidence: 78%
“…P‐UiO‐66(200) has a higher weight loss because of foreign organic compounds derived from the grafted TDPA molecules on the material surfaces. Previous studies have reported a similar common phenomenon after introducing new guest organic species in MOFs [2b,15a,26] . TGA analysis results confirm the successful grafting of TDPA on UiO‐66.…”
Section: Resultssupporting
confidence: 78%
“…Post-synthetic MOFs with introduced various functional groups were able to be used for adsorptions 153–155 of CO 2 , 3,118,156 H 2 , 157 SO 2 , 158 ammonia, 159,160 toxic dyes, 161–166 radioactive contaminants, 59 heavy metal ions, 5,91,167,168 and biomacromolecules. 169 Studies demonstrated that post-synthetic MOFs were promising to be applied as drinking water cleaners for water purification.…”
Section: Applicationsmentioning
confidence: 99%
“…5 Among them, the adsorption method has attracted wide attention due to its advantages, such as simple operation, high efficiency, and environmental friendliness. [6][7][8] Zeolite-imidazolate-8 (ZIF-8), as a classical metal-organic framework (MOF) material, has the advantages of a high specific surface area, high thermal stability, and open metal sites. 9,10 Furthermore, the synthesis of ZIF-8 is simple and requires mild conditions, and it exhibits excellent adsorption performance in organic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…5 Among them, the adsorption method has attracted wide attention due to its advantages, such as simple operation, high efficiency, and environmental friendliness. 6–8…”
Section: Introductionmentioning
confidence: 99%